2017
DOI: 10.3389/fmars.2016.00286
|View full text |Cite
|
Sign up to set email alerts
|

A Model Simulation of the Adaptive Evolution through Mutation of the Coccolithophore Emiliania huxleyi Based on a Published Laboratory Study

Abstract: We expect the structure and functioning of marine ecosystems to change over this century in response to changes in key ocean variables associated with a changing climate. Organisms with generation times from years to decades have the capacity to adapt to changing environmental conditions over a few generations by selecting from existing genotypes/phenotypes, but it is unlikely that evolution through mutation will be a major factor for organisms with generation times of years to decades. However, phytoplankton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…However, because LT modifications are reversible, the fitness benefits and trait changes from LT modifications will be lost from the population more quickly than would be expected from HT modifications alone, especially in a dynamic environment where selective pressure can fluctuate. Theoretical (8,17) and empirical (9,12) data suggest that HT and LT modifications acting together best explain patterns of microbial evolution on timescales of hundreds of generations. For example, experimental evolution studies in yeast have shown that the interaction of short-term epigenetic inheritance with genetic mutation modifies the rate and type of adaptation, thereby impacting long-term evolution (12).…”
Section: Significancementioning
confidence: 99%
“…However, because LT modifications are reversible, the fitness benefits and trait changes from LT modifications will be lost from the population more quickly than would be expected from HT modifications alone, especially in a dynamic environment where selective pressure can fluctuate. Theoretical (8,17) and empirical (9,12) data suggest that HT and LT modifications acting together best explain patterns of microbial evolution on timescales of hundreds of generations. For example, experimental evolution studies in yeast have shown that the interaction of short-term epigenetic inheritance with genetic mutation modifies the rate and type of adaptation, thereby impacting long-term evolution (12).…”
Section: Significancementioning
confidence: 99%
“…As such, the biogeographic provinces of phytoplankton assemblages in the Southern Ocean are likely to shift spatially or change fundamentally in the coming decades (Deppeler and Davidson, 2017). On longer timescales, a persistent new set of environmental conditions may drive evolutionary adaptation of existing species (Denman, 2017). Changes in NPP and phytoplankton species composition influence many biogeochemical processes, such as the magnitude and stoichiometry of nutrient uptake and recycling (Arrigo et al, 1999;Weber and Deutsch, 2010; Section "Changes in Macronutrient Biogeochemistry") and carbon transfer to higher trophic levels (Section "Carbon Transfer and Storage in Pelagic and Benthic Food Webs").…”
Section: Projected Changes In Phytoplankton Species Composition and Dmentioning
confidence: 99%
“…This raises the question of the timescale of such experimental detection studies. Furthermore, a recent theoretical paper concluded that in a large population of ∼10 5 individuals, the time for a single favourable mutation to reach a significant (and thus detectable) fraction of the population may take between 30 and 140 generations (Denman, ). Alternatively, epigenetically facilitated mutations can emerge more rapidly in large populations such as in microbes.…”
Section: All Roads Lead To Genes Via the Epigenetic Hubmentioning
confidence: 99%